2018
DOI: 10.1186/s12909-018-1407-8
|View full text |Cite
|
Sign up to set email alerts
|

Graduate medical education scholarly activities initiatives: a systematic review and meta-analysis

Abstract: BackgroundAccording to the Accreditation Council for Graduate Medical Education residents “should participate in scholarly activity.” The development of a sustainable, successful resident scholarship program is a difficult task faced by graduate medical education leadership.MethodsA medical librarian conducted a systematic literature search for English language articles published on scholarly activities initiatives in Graduate Medical Education (GME) between January 2003 and March 31 2017. Inclusion criteria i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 47 publications
1
54
2
1
Order By: Relevance
“…Perhaps filling knowledge gaps with interventions like the CRW and The Recipe guidebook are necessary but insufficient to increase resident scholarship, and resident peer leaders allow residents to overcome the uncertainty barriers to scholarly activity described by Ledford et al 6 A qualitative study may help identify a correlation, and would also help identify other characteristics of the culture of scholarship that appears to be a common theme across successful scholarly activity interventions. 8 Other limitations to our study include short follow-up time, which may explain why conference participation increased, but longer lead time outcomes like textbook chapters and research participation did not.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Perhaps filling knowledge gaps with interventions like the CRW and The Recipe guidebook are necessary but insufficient to increase resident scholarship, and resident peer leaders allow residents to overcome the uncertainty barriers to scholarly activity described by Ledford et al 6 A qualitative study may help identify a correlation, and would also help identify other characteristics of the culture of scholarship that appears to be a common theme across successful scholarly activity interventions. 8 Other limitations to our study include short follow-up time, which may explain why conference participation increased, but longer lead time outcomes like textbook chapters and research participation did not.…”
Section: Discussionmentioning
confidence: 89%
“…6 Myriad strategies have been developed within specific programs to overcome barriers to scholarly activity. 7,8 Most of these strategies focus on overcoming the specific barriers listed above, and were well described by Seehusen and Weaver in 2009 across many programs, 9 and Alweis et al in 2015 as iterative improvements within a single program. 10 One successful alternative approach has been a scholarly activity point system, first described by Seehusen et al in 2009, 11 and later shown to be successful at several other programs.…”
mentioning
confidence: 99%
“…Mentorship is an influential factor in a thriving research experience. 10,20,24,25 Prior studies have reported a lack of proper mentoring as a significant barrier for research. 4,8 Residents of TUOMS were less motivated to do research due to 1) mandatory research topics and 2) advisors/ mentors.…”
Section: Discussionmentioning
confidence: 99%
“…1,11,12 Reported barriers include limited time, little funding, difficulty identifying mentors, and insufficient technical support. [13][14][15][16] Although survey research revealed program characteristics related to scholarship success, [17][18][19][20][21] it cannot provide a rich understanding of residency leadership perspectives on scholarship. Qualitative inquiry into how leaders perceive these requirements and how they communicate about requirements can provide deeper understanding of leader perspectives.…”
Section: Reportsmentioning
confidence: 99%